The students’ mathematical communication ability taught by cooperative script types at SMP Negeri 3 Kisaran - Dwi Maulida Sari (Journal of Didactic Mathematics, 2022)
Mathematical communication ability is important owned by students’ because a lack of ability of mathematical communication can lead to a lack of understanding of the mathematical concept or mathematical problem. Preliminary observation conducted by researchers in SMP Negeri 3 Kisaran found that the students aren’t able to answer. It is clearly seen in the student’s answer sheet that the student’s mathematical communication ability is low lack of student’s mathematical communication ability of SMP N 3 Kisaran is so related to the learning process which has been done by the mathematics teacher. To fix it is necessary to develop an approach to learning that is more effective, creative, and fun. On this basis, the authors try to apply cooperative learning Control Class type to improve mathematical communication ability. This research is quasi-experimental or quasi-experimental research with a quantitative approach. The conclusion found that there is an increase in students’ mathematical communication ability taught by cooperative learning cooperative script type at SMP Negeri 3 Kisaran.